울주군 농업·농촌 종합 발전계획 연구 - 박문호 (한국농촌경제연구원, 2005)
The changing environments of world agriculture, such as an opening of agricultural market, Free Trade Agreements between countries, and policies focusing on multilateral functions of agriculture, affects greatly on the Korean agriculture and its policies. Especially, in Korea, local governments' investment and interest toward agriculture determines the quality of life in the rural community, competitiveness of each agricultural product, and income level of individual farm. Thus, adopting and implementing agricultural plans by the local autonomous entities are being important. The main purpose of this study is 1) to examine regional, environmental, and socio-economic characteristics of agriculture and rural communities in the entire Ulju-gun area, 2) to adopt comprehensive development plans for the agriculture and rural communities in the Ulju-gun by assessing strong and weak points, and potentials of the area. Consists of eight Myeons out of four towns, the Ulju-gun could be identified as a city and rural composite county and a suburb region around a metropolitan area. In particular, the Ulju-gun has a potential to promote a specialized premium rice brand with its existing eco-friendly rice production complex. However, the area needs to improve supplying superior rice breeds and rice processing systems. The region has specialized crops such as pears and sweet persimmons. Recently, the production of leeks, dropworts, and paprika has been increased in the reason, but the volume is still limited. Korean beef cattle product of the region is famous. For the reason, the region is trying to introduce a "Special Roasted Korean Beef Cattle Zone" in Bonggye and Eonyang area. However, increasing land prices makes it difficult to realize economy of scale and new entry in livestock industry. For the distribution of the agricultural products, the region is not performing well because most of its Agricultural Products processing Centers are small-scaled and dispersed. Furthermore, the level of consumers' recognition on its products is low because brand marketing strategies are not integrated but focus on individual brands. In the meantime, Ulju-gun is consists of rural communities, mountain, and fishing villages, and blessed with abundant wonderful natural landscapes like Alps of Youngnam and tourism resources. Nevertheless, only a handful of farm households are participating in tourism projects utilizing these rich resources. Living standards of rural communities are better than average of other counties'. In addition, the community is actively engaged in sisterhood relationships with adjacent businesses and has many employment opportunities other than agriculture. Given situations, Ulju-gun needs to construct a Green Park for the future development of agriculture and rural communities. The term Green stands for an establishing agricultural industry producing specialized quality eco-friendly products, while 'Park' refers to rest and living space offering safe foodstuffs with tourism attraction. In order to realize the vision of Green Park, 1) choice and concentration of specialized farming, 2) construction of local distribution infrastructure and integrating brands with quality goods, 3) creating pleasant living environment, and 4) establishment of mutually beneficial economic models between rural and urban areas which will spearhead changes are necessary. From the above mentioned strategies, the comprehensive development plans could be summarized as follows: 1) Establishing rice production and distribution systems based on Rice Processing Complex (RPC). In detail, introducing eco-friendly and premium brand rice through establishment of processing and distribution infrastructures on Dubuk and Ungchon RPC. 2) Setting up a production complex of specialized crops of the region including pear, sweet persimmon, and other growing products. 3) Developing a premium Korean beef cattle brand with linkage to the "Special Roast Korean Beef Cattle Zone" in Bonggye and Eonyang area. Also, the area needs to promote eco-friendly livestock industry through naturally circular stock breeding. 4) Introducing eco-friendly projects over very wide areas. To do so, it is recommended that Dudong area is suitable for a pilot project. With a result from the pilot project, the project could be conducted in overall Ulju-gun. 5) Enhancing distribution system at places of production from an establishment of centralized and integrated APC in Ulju-gun to enable large scaled, standardized, and premium brands fruit farming. To this end, it is desirable to build a regional APC at Ungchon area as a crossroads between Busan and Onnyang area. 6) Building and promoting an industrialization of Green Life by capitalizing the geographical advantage of Ulju-gun to increase farm visits and interactions between rural and urban areas. For example, creating an agricultural theme park and various weekend farms, developing candidate sites of Green Farming Experience Town and enhancing tourism resources in farming and fishing communities are recommended. 7) Developing the region as a pleasant and convenient place of settlement not only for existing residents but also for city dwellers. To do so, a comprehensive town development project is necessary including an improvement of living, production, and natural condition. 8) Establish education systems and enhancing the quality of education for the elite farmers to prepare a coming knowledge-based agricultural era.